Expression of SARS‐CoV‐2 entry factors in human oral tissue. Issue 6 (9th January 2021) - Sawa, Yoshihiko; Ibaragi, Soichiro; Okui, Tatsuo; Yamashita, Junro; Ikebe, Tetsuro; Harada, Hiroyuki
Abstract: The distribution of cells expressing SARS‐CoV‐2 entry factor angiotensin‐converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) in human oral tissues were tested. The investigation was conducted with normal flesh tissue and paraffin‐embedded specimens. The ACE2 and TMPRSS2 expression was detected with all subjects in the normal mucosa of the keratinized stratified squamous epithelia of the tongue and non‐keratinized stratified squamous epithelia of the lip and cheek. It was found that ACE2 is expressed in the cytoplasm and on the cell membrane mainly in the stratum granulosum of the epithelia while the TMPRSS2 is strongly expressed on the cell membrane mainly in the stratum granulosum and stratum spinosum, but not in the stratum basale. Antibodies' reactions for ACE2 and TMPRSS2 were not observed in the nuclei or keratin layer. The expression of ACE2 and TMPRSS2 in the oral epithelia appears to be general, and the expression was also observed in the mucous and serous acini of the labial glands. The SARS‐CoV‐2 may transiently attach to the oral mucosa and the minor salivary glands which are present under all of the oral mucosa. The oral cavity can be considered an important organ for SARS‐CoV‐2 attachment and may provide a preventive medical avenue to guard against COVID‐19 by preventing saliva from scattering. Abstract : The ACE2 and TMPRSS2 expression was detected in the tongue, lip and cheek, and observed in the mucous and serous acini of the labial glands. The expression of the ACE2 and TMPRSS2 in the oral cavity appears to be general. The oral cavity can be considered an important organ for the SARS‐CoV‐2 adhesion and may provide a preventive medical avenue against COVID‐19 by preventing saliva from scattering.